Significantly Better Efficacy for Acute Ankle Gouty Arthritis Through Arthroscopic Debridement Compared With Simple Drug Therapy: A Longitudinal Study With 1-Year Follow-up. Issue 1 (14th December 2020) - Tang, Bo; Zeng, Xuezhu; Fan, Cheng
Abstract : Objective: The aim of this study was to compare the clinical feasibility, efficacy, and cost economics of simple drug therapy with a combination therapy of arthroscopic debridement and drug treatment of ankle acute gout arthritis. Methods: Patients with acute ankle gout arthritis hospitalized in our department from January 2017 to August 2019 were included. Among them, 32 patients who received arthroscopic debridement in a special floating position and drug therapy were included into the observation group, and 24 patients who received drug treatment alone were included into the control group. The American Orthopaedic Foot & Ankle Society (AOFAS) ankle-hindfoot score, the effective rate, the recurrent rate, stay of hospital, complications, and cost economics were compared between these 2 groups at postoperative 48 hours, discharge time, and 1 year. Results: The basic data and AOFAS ankle-hindfoot score before treatment showed no significant difference ( p > 0.05) between these 2 groups. Compared with the control group, the observation group showed significantly higher AOFAS score at postoperative 48 hours (80.73 ± 9.15 vs 71.09 ± 8.54, p = 0.000), discharge time (87.73 ± 9.92 vs 77.71 ± 10.26, p = 0.000), and postoperative 1 year (85.92 ± 10.39 vs 76.36 ± 8.72, p = 0.000); lower recurrence rate (15.63% vs 25%, p = 0.382); significantly shorter length of hospitalization (4.92 ± 0.88 days vs 8.90 ± 0.73 days, p = 0.000); and significantly higher cost (¥8981.2 ± ¥740.2 vs ¥3558.3 ± ¥270.1, p = 0.000) during the discharge time. Conclusions: Ankle gout arthritis could be systematically and safely managed with ankle arthroscopic technique in special floating position. In addition, compared with conservative drug therapy alone, ankle arthroscopic debridement combined with conservative drug therapy improved clinical efficacy, lowered recurrence rate, and shortened length of hospitalization.